The New Priorities of the European Union Migration Policy - Pavlov, Atanas (Research Papers, 2022)
The aim of the research is to critically comment the New Pact on Migration and Asylum of the European Union, which introduces a new principle of flexible solidarity, consisting of two opposite characteristics – on the one hand – mandatory solidarity and on the other – a flexible one. Member States’ quotas will be replaced by flexible contribution to various aspects of the migration policy, which will allow countries that refuse to accept migrants to support the so-called first-line countries. The result of the research is a generalization and analysis of the new Migration Pact, which covers all areas of migration issues and applies a single approach and harmonizing of existing European legislation in the field. Other part of the results of the research analyse the new Multiannual Financial Framework of the European Union which foresees an increase in the migration and border management spending up to 22.7 bln. euro and an increase in the field of security and defence spending up to 13.2 bln. euro.